2018 Fluid Dynamics Conference 2018
DOI: 10.2514/6.2018-3732
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Performance of Finite-Span Pitching Propulsors in Side-by-Side Arrangements

Abstract: Experimental measurements are presented on the performance of two finite-span pitching wings with an aspect ratio of AR = 2 interacting in a side-by-side arrangement. Experiments are conducted for various synchronies and cross-stream spacings. The thrust, power and lift coefficients as well as the efficiency are reported for both the individual wings and the collective. The collective thrust and power consumption are found to increase while the efficiency decreases during out-of-phase oscillations (φ = π) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Yet, both the spatial organization (3,8) and temporal synchronization (9)(10)(11) have emerged as major drivers of the hydrodynamic interactions, and, consequently, the energetic cost of locomotion and traveling speed of individuals in a collective. Still, our understanding of the force production and energetics of schooling swimmers is mostly limited to canonical spatial arrangements such as a leader-follower in-line arrangement (12)(13)(14)(15) and a side-by-side arrangement (11,(16)(17)(18), while there are fewer studies of staggered arrangements (19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Yet, both the spatial organization (3,8) and temporal synchronization (9)(10)(11) have emerged as major drivers of the hydrodynamic interactions, and, consequently, the energetic cost of locomotion and traveling speed of individuals in a collective. Still, our understanding of the force production and energetics of schooling swimmers is mostly limited to canonical spatial arrangements such as a leader-follower in-line arrangement (12)(13)(14)(15) and a side-by-side arrangement (11,(16)(17)(18), while there are fewer studies of staggered arrangements (19)(20)(21)(22).…”
mentioning
confidence: 99%
“…An inappropriate selection of these factors might result in 50% performance reduction. Furthermore, several studies (Dewey et al, 2014;Dong and Lu, 2007;Huera-Huarte, 2018;Kurt and Moored, 2018) have reported an enhancement in thrust generation with an improvement in propulsive efficiency when two propellers were arranged in staggered or side-by-side formations with in-phase pitching. With their out-of-phase or anti-phase pitching, hydrodynamic efficiency remained almost the same with greater thrust forces and more power consumption for Reynolds number between 4000-11000.…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that the transition from drag to thrust producing wakes occurred at smaller Strouhal numbers for shorter spacing distance between foils. In another study, Kurt and Moored (2018) presented that propellers pitching synchronously attained a better performance in terms of 20% more thrust and 17% better efficiency with phase differences of π/2 and 3π/2 when the separation distance was equal to one chord-length. In their study, trends in the variation of power did not coincide with those for thrust, thus leading to a disagreement with the observations by Dewey et al (2014) in this context.…”
Section: Introductionmentioning
confidence: 99%
“…These highly three-dimensional spatial configurations found within collectives can be decomposed into canonical in-line, side-by-side, or tip-to-tip arrangements as presented in Figure 1 . To date, these interactions have mostly been studied for propulsors in in-line arrangements [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], although a few efforts have been made to understand interactions in side-by-side arrangements [ 20 , 21 , 22 , 23 ], as well as staggered arrangements [ 24 , 25 , 26 , 27 ]. Here, our focus is on the propulsive performance and flow interactions in in-line , and staggered arrangements.…”
Section: Introductionmentioning
confidence: 99%
“…Including hydrodynamic interactions in a model of a fish school is a challenging task without simplifications made with theoretical approximations [ 28 ]. Our current understanding of flow interactions and energetics within fish schools is mostly based on two-dimensional flow analyses [ 10 , 11 , 12 , 13 , 14 , 20 , 21 , 24 , 25 , 29 , 30 ], but there are far fewer three-dimensional studies focusing on these interactions that employ finite-span wings or hydrofoils, or fish-like bodies [ 15 , 19 , 22 , 25 , 31 , 32 ]. Amongst these studies, some consider the interaction of an oscillatory body with a classic drag-producing von Kármán street [ 30 , 33 ], and the others consider an interaction with a thrust-producing reverse von Kármán street [ 12 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%